Gut Microbiota, Circulating Metabolites and Risk of Endometriosis: A Two-Step Mendelian Randomization Study - Yang Hua (Polish Journal of Microbiology)
Epidemiological studies and animal models have suggested a possible link between gut microbiota (GM), circulating metabolites, and endometriosis (EMs) pathogenesis. However, whether these associations are causal or merely due to confounding factors remains unclear. We conducted a two-sample and two-step Mendelian randomization (MR) study to elucidate the potential causal relationship between GM and EMs, and the mediating role of circulating metabolites. Our MR analysis revealed that higher abundances of class Negativicutes, and order Selenomonadales, as well as genera Dialister, Enterorhabdus, Eubacterium xylanophilum group, Methanobrevibacter were associated with an increased risk of EMs (Odds Ratio (OR) range: 1.0019–1.0037). Conversely, higher abundances of genera Coprococcus 1 and Senegalimassilia were linked to reduced risk of EMs (OR range: 0.9964–0.9967). Additionally, elevated levels of circulating metabolites such as 1-eicosatrienoyl-glycerophosphocholine and 1-oleoylglycerophosphocholine were found to be associated with heightened risk of EMs (OR range: 2.21–3.16), while higher concentrations of 3-phenylpropionate and dihomo-linolenate were protective (OR range: 0.285–0.535). Two-step MR analysis indicated that specific microbial taxa, notably genus Enterorhabdus and order Selenomonadales, might function as mediators linking circulating metabolites to the risk of EMs. Our findings suggest a probable causal relationship between GM, circulating metabolites, and EMs, indicating that GM may mediate the influence of circulating metabolites on the pathophysiology of EMs. These results offer new leads for future mechanistic studies and could inform clinical translational research.